(untitled) (Contemporary Journal of Social Science Review, 2025)
This study investigates the implications of the exogenous shock caused by pandemic crisis on audit pricing in Pakistan. The financial uncertainty associated with the pandemic crisis represents the most significant threat to audit practitioners and their clients since the global financial crisis of 2007–2008. For this investigation, we focus on a sample of all non-financial firms listed on Pakistan Stock Exchange (PSX) between 2017 and 2021, inclusively. The empirical results show that audit clients paid higher audit fees during the crisis compared to the prior years. These findings support the view that the increase in audit fees is essentially due to heightened business risk and the additional audit efforts required to maintain the quality of audit services amidst the crisis. This study, therefore, contributes to the audit pricing literature by providing evidence from Pakistan. The findings of this study may be of interest to corporate stakeholders as well as audit practitioners.